IMPLEMENTATION OF ROBSON'S CLASSIFICATION SYSTEM IN THE SECOND LARGEST HOSPITAL IN NORTH MACEDONIA - FIRST RESULTS - Skeparovska, Kristina; Kocevska, Ana; Mitevska, Maja; Atanasovska, Lidija Kalanoska; Koprivnjak, Ivan (Journal of Morphological Sciences; Vol 7 No 1 (2024): JMS, 2024)
The number of pregnant women that gave birth via cesarean section (c-section, c/s) increases constantly through years all over the world.  Analyzing and revising the major indications that urge c-section did not reduce its number. Introduction of new classification by Robson, that allows categorizing of each pregnant woman into appropriate group is a new attempt and tool for achieving this goal. All pregnant women who gave birth in Specialized Hospital for gynecology and obstetrics â€œMother Teresaâ€ from 01.01.2021 till 31.12.2021 and from 01.01.2016-31.12.2016 were enrolled in this study. The data regarding the obstetrics characteristics, the course of labor as well as the mode of delivery and the main indications for C-Section were collected retrospectively from hospital records and the subjects were classified into appropriate Robson group. The total number of C-Section deliveries in 2021 was 13.8% higher than in 2016 reaching 41% of all deliveries.  The major contribution to C/S rate with 33.4% was made by R5A group, followed by R2B group (prelabor C/S in nulliparous women) with 16.5%, and R1 group (nulliparous women with spontaneous onset of labor) with 14.2%. The exclusive mode of delivery by c-section, with none vaginal birth was seen in R6 and R7 (along with R9 group). Almost exclusive mode of delivery with c-section, with a rate above 95% was recorded in R5 and R8 group.  The two leading causes for C-Section in women with spontaneous onset of labor regardless of parity were: failed induction and functional dystocia. The main reason in nulliparous women for prelabor c-section was pregnancy achieved by in vitro fertilization, while in multiparous (R4B group) -placenta previa was the most common cause. The obstetricians should be encouraged to undertake TOLAC, and encouraged not to refrain from vaginal birth in breech presentation pregnancy and vertex twin pregnancy. The methods for induction of labor should be revised.  The indications for c-section should be revised. Key words : Robson classification, c-section, IOL, TOLAC.